Influence of refractory organic matter on source rock hydrocarbon potential: A case study from the Second White Specks and Belle Fourche formations, Alberta, Canada. (August 2017) - Synnott, Dane P.; Dewing, Keith; Sanei, Hamed; Pedersen, Per Kent; Ardakani, Omid H.
Abstract: Dilution by inert, refractory organic carbon can have a significant impact on the hydrocarbon potential of source rocks. In this study, a correction of total organic carbon, based on petrographic observations, is proposed to give a better indication of hydrocarbon generation potential. This correction shows that although the Second White Specks Formation is an excellent hydrocarbon source rock, hydrogen index and total organic carbon are influenced by dilution from refractory organic carbon of various sources. The results show that a higher degree of dilution occurs within the Belle Fourche Formation than the Second White Specks Formation. This dilution can have a significant impact on the hydrocarbon potential of the rock. Volumetric calculation of the inert carbon fraction using organic petrographic methods provides a semi quantitative method to correct total organic carbon values for the refractory organic carbon dilution effect. Incorporation of the dilution corrected organic carbon value in hydrogen index calculations allows a greater understanding of source rock hydrocarbon potential. This method provides better differentiation of the small scale variation between micro-facies and formation, as observed in the Second White Specks and Belle Fourche formations, than traditional bulk geochemical methodologies and previously proposed correction methodologies. Degree of dilution, either through transport of recycled allochthonous or autochthonous reworking of organic matter in-situ is highly variable and represents a significant challenge in the characterization of heterogeneous source rocks. This study investigates the organic petrology and geochemistry of a sediment core from the thermally immature area of the Upper Cretaceous Second White Specks Formation and Belle Fourche Formation. Reflectance and relative abundance of three maceral groups (bituminite, alginite, and refractory organic carbon macerals) showed significant organic matter compositional differences between micro-facies in the Second White Specks Formation. A change is also observed in organic matter composition from the upper part of the Belle Fourche Formation to the Second White Specks Formation. These compositional changes represent shifts in sediment source, sea floor oxygen levels, and depositional energy levels. These changes can be episodic, as observed between micro-facies, or longer time scale trends, as observed between the studied formations. Highlights: Dilution from refractory carbon results in a drastic impact on petroleum potential. Calculation of dilution correction gives a better indication of petroleum potential. Difference observed in organic matter composition between studied formations. Shift in organic matter composition matches shift in depositional environment. Bacterial degradation impacts the reflectance of refractory organic carbon macerals.